CONTRACT RELAX STRETCHING DAN ULTRASOUND THERAPY LEBIH EFEKTIF MENURUNKAN NYERI DIBANDINGKAN ISCHEMIC COMPRESSION TEHNIQUE DAN ULTRASOUND THERAPY PADA PASIEN TENSION HEADACHE - Muh. Asri; Susy Purnawati; Sugijanto - (Sport and Fitness Journal, 2016)
Activities sat and looked in a long time tend to occur spasms in the neck muscles, causingpain in the neck and head, known as tension headaches. To reduce the pain of tension headacheswith the intervention of a combination of ultrasound and ischemic compression technique and acombination of ultrasound and intervention contract relax stretching. The purpose of this studyprove that the intervention ultrasound and contract relax stretching is more effective thanintervention ultrasound and ischemic compression technique in reducing the painful tensionheadaches. This research method is the true experimental with pre and posttest control groupdesign. This research was conducted for two months and the place of research in hospitalsBuleleng. Samples are patients who seek treatment in medical rehabilitation installations inhospitals Buleleng aged 35-45 years with the number of 32 samples are divided into two groups,in which the treatment group I (n = 16) and treatment group II (n = 16). Using measurementinstruments Neck Pain Disability Index (NPDI). The results of this study showed a meantreatment group I before treatment 91,56 and standards (SB) 8,91, average 35,25 after treatmentand SB 15,96 with p = 0.00 (p <0.05). This means intervention ultrasound and ischemiccompression technique effectively lowers tension headache pain. The results mean treatmentgroup II before treatment 91,12 and SB 6,95, and after treatment 13,62 the average SB 10,78 withp = 0.00 (p < 0.05). This means intervention ultrasound and contract relax stretching effectivelyreduce the pain of tension headaches. Test after intervention difference between treatment groupsI and II after intervention treatment groups using Mann withney U-Test p = 0:01 (p <0.05). It isproved that a decrease in pain tension headaches in both treatment groups there were significantdifferences. It is concluded that ultrasound and contract relax stretching is more effective thanultrasound and ischemic compression technique in reducing tension headache pain.